"From Traditional 'Urf to Digital 'Urf: Accommodating the Values of the Young Generation on Husband-Wife Relations in the Framework of Ushūl al-Fiqh". - Zulbaidah, Zulbaidah; Yuniardi, Harry; Januri, Januri; Najmudin, Nandang; Cason, Christoper (AL-ISTINBATH : Jurnal Hukum Islam, 2025)
This study examines how digital interpretations of marital roles among Muslim youth transform the classical concept of 'urf and challenge traditional gendered norms in Islamic family law. Existing research has extensively discussed 'urf and marital hierarchy, yet little attention has been paid to how digital-native perceptions, circulating through platforms such as TikTok and Instagram, reshape normative expectations of spousal relations within the framework of ushul fiqh. This study addresses this gap by analyzing the emergence of "digital 'urf" as a new sociocultural reference for young Muslims. Using qualitative documentary analysis combined with thematic content analysis, the study examines 120 short-form digital contents produced by Indonesian Muslim youth between 2023–2024, selected through purposive sampling. The dataset is triangulated with classical fiqh texts, contemporary fatwas, and statutory family law materials to evaluate the extent to which digital 'urf aligns with or diverges from established ushul fiqh principles. The findings reveal three major shifts: (1) digital 'urf reframes marital roles from hierarchical–patriarchal to partnership-based, (2) normative authority moves from textual and communal scholars to digital micro-influencers, and (3) the concept of qiwāmah undergoes functional reinterpretation driven by economic and technological equality. These shifts indicate the emergence of a hybrid normativity that merges experiential digital ethics with fiqh-based reasoning. This study contributes a conceptual reformulation of 'urf in the digital era and offers a framework for integrating digital socio-cultural patterns into ushul fiqh analysis.